THE IMPACT OF AQIDAH AKHLAK LEARNING ACHIEVEMENTS ON STUDENT ETHICAL DEVELOPMENT AT AL-KHAIRIYAH ISLAMIC HIGH SCHOOL, MAMPANG PRAPATAN, JAKARTA - Saiful Anwar; Abdiah Salamah; Syarifah Syarifah; Muwahidah Nurhasanah (Universitas Islam Lamongan, 2023)
Ethical values are crucial for individuals in society as they shape their behavior and actions. Failing to instill ethics in people's lives may result in a materialistic mindset that prioritizes worldly gains above all else. Ethics and morals play a significant role in everyday life, guiding individuals in their interactions and decision-making processes. Several factors contribute to the decline of ethics among adolescents, including family disharmony, weak self-identity and self-control, unhealthy mental attitudes, disillusionment, the influence of social media, and economic pressures that may lead to immoral behaviors. This study aims to explore the impact of learning outcomes in the subject of moral creed on students' ethics at MA Al-Khairiyah in Mampang Prapatan, South Jakarta. A quantitative research approach was employed, using a survey method for data collection through questionnaires and documentation. Data analysis encompassed descriptive analysis, prerequisite analysis testing, and hypothesis testing. The study focused on Class X students at MA Al-Khairiyah as the population and sample. The findings revealed that the learning outcomes in the moral creed subject significantly influenced the formation of student ethics, accounting for 54.8% of the variance. The remaining 45.2% was influenced by other variables not investigated in this study. The significance level of 0.000 (< 0.05) indicated a substantial influence of learning outcomes on the development of ethics related to the moral creed subject. The researchers' calculations yielded a t-value of 3.069, surpassing the critical t-value of 1.666. Consequently, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted